Penerapan Model Pembelajaran Treasure Hunt Math untuk Meningkatkan Hasil Belajar Matematika pada Materi Pecahan Kelas V UPTD SD Negeri 85 Parepare) - Zaid Zainal; Nurul Mukhlisa; Anggita Nurfajarini (MASALIQ, 2026)
Improving the mathematics learning process and outcomes in fractions requires a learning model that can promote students’ active engagement. This study aimed to describe the implementation process of the Treasure Hunt Math learning model and improve Grade V students’ mathematics learning outcomes in fractions at UPTD SD Negeri 85 Parepare. The study employed a qualitative approach with a Classroom Action Research design conducted over two cycles. The participants comprised 34 Grade V students, while one classroom teacher acted as an observer. Data were collected through observation, learning achievement tests, and documentation and were subsequently analyzed using qualitative descriptive methods through data condensation, data presentation, and conclusion drawing and verification. The results showed that the implementation of Treasure Hunt Math improved the students’ mathematics learning process and outcomes. In Cycle I, the learning process and outcomes remained in the adequate category because the teacher and students were still adapting to the implemented model. Following improvements in Cycle II, the learning process became more active, collaborative, and enjoyable, accompanied by an increase in learning mastery to the good category. These findings confirm that Treasure Hunt Math can be used as an alternative learning model to improve students’ engagement and mathematics learning outcomes, particularly in fractions at the elementary school level.